Effects of integrated improving technique pilates and bodyflex level of functionality on students - Kozina, Zh.L.; Ilnizaya, A.S.; Kolomiez, N.A.; Barybina, L.N.; Cieślicka, Mirosława; Stankiewicz, Błażej; Pilewska, Wiesława (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: To identify the influence of complex application procedures bodyflex and pilates using information and communication technologies on the students’ level of functionality. Material : The study involved 46 students. Measured indicators: blood pressure, stroke volume, heart rate at rest and during exercise. Identify indicators of submaximal performance, autonomic balance. Results : There was a significant increase in young stroke volume - from 58 ml. to 62.1 ml., the threshold of anaerobic metabolism of 123.4 beats/min to 141.4 beats/min. The girls showed a significant increase in stroke volume - from 58.3 ml to 62.5 ml., the threshold of anaerobic metabolism of 123.7 beats/min. to 143.3 beats/min. Found an increase in performance power supply systems (S.A. Dushanin technique). Marked improvement in efficiency of the cardiovascular system (increased heart rate variability from 322.12 ms to 354.43 ms, reduced mode amplitude values of RR-intervals from 34.09 % to 21.54 %. Submaximal increase of capacity of students. Conclusions : complex application systems bodyflex and pilates enhances the functionality students.